Shannon Vallor's Wise Polemic against AI Enthusiasm - Parens, Erik (The Hastings Center report, 2025)
In The AI Mirror: How to Reclaim Our Humanity in an Age of Machine Thinking, Shannon Vallor excavates the moral significance of the difference between experiences such as cognition, empathy, and love that emerge in embodied beings like us, and simulacra of those experiences as produced by bodiless systems like generative AIs. She argues, helpfully and powerfully, that there is no greater existential threat to humanity than failing to remember and preserve that difference.